The Influence of Electronic Word of Mouth (E-Wom) and Brand Image on Purchasing Decisions for Gaga Instant Noodles in Surabaya City - Aulya, Deta Riza; Aminah, Siti (Formosa Journal of Multidisciplinary Research, 2024)
The aim of this research was to identify and analyze the effect of electronic word-of-mouth and brand image on purchasing decisions for Gaga instant noodles in Surabaya city. This research uses quantitative research methods. Data collection was carried out through distributing questionnaires and using aKLikert scale. Data analysis uses the Structural Equation Model (SEM) method via SmartPLS 3.0 software. The research results show that electronic Word-of-mouth and brand image were able to contribute well to consumer purchasing decisions for Gaga instant noodles in Surabaya city.